(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe treatment adherence among tuberculosis patients managed at Viet Tiep Hospital, Hai Phong, in 2023 and to analyze several associated factors. Methods: A cross-sectional descriptive study was conducted on 192 tuberculosis patients receiving treatment at Viet Tiep Hospital from September to December 2023. Data were collected through direct interviews using a structured questionnaire. Results: The overall treatment adherence rate was 72.4%. Adherence to scheduled follow-up visits was 97.4%, correct medication dosage was 91.7%, regular medication use for the full treatment duration was 86.5%, adherence to periodic laboratory testing was 81.3%, and correct medication administration was 75.5%. Factors significantly associated with higher treatment adherence included age ≥60 years (OR = 2.09; 95%CI: 1.06–4.10; p = 0.03), not living with a spouse (OR = 3.37; 95%CI: 1.12–10.09; p = 0.02), regular family support for follow-up visits and laboratory tests (OR = 2.70; 95%CI: 1.33–5.49; p = 0.04), and adequate, on-time supply of anti-tuberculosis drugs (OR = 2.77; 95%CI: 1.14–6.75; p = 0.02). Conclusion: Treatment adherence among tuberculosis patients at the study site was relatively high; however, limitations remained in proper medication administration and adherence to periodic laboratory testing. Strengthening counseling, family support, and continuity of drug supply may help improve adherence.